2020
DOI: 10.3390/membranes10110321
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Naturally Occurring Strontium by Nanofiltration/Reverse Osmosis from Groundwater

Abstract: Removal of naturally occurring strontium (Sr) from groundwater is vital as excessive exposure may lead to bone growth problems in children. Nanofiltration/reverse osmosis (NF/RO) is commonly used in groundwater treatment due to the high effectiveness and simple maintenance of these pressure driven membrane processes. In this research, a pilot-scale NF/RO system was used to desalinate a natural groundwater sample containing high Sr concentration (10.3 mg/L) and “old” groundwater organic matter (70.9 mg/L) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…The permeate water of NF and RO are mixed to form the final permeate water. Cai et al constructed a pilot-scale NF-C-RO system to desalinate natural ground brackish water containing high Sr concentration (10.3 mg/L) in Tanzania [ 130 ]. It was found that the NF unit only had a Sr rejection of 55–67%, while RO can remove almost 100% of Sr, so the mixture of NF permeate and RO permeate can meet the USEPA guideline of 1.5 mg/L.…”
Section: Combined Utilization Of Nf With Other Membrane Technologymentioning
confidence: 99%
“…The permeate water of NF and RO are mixed to form the final permeate water. Cai et al constructed a pilot-scale NF-C-RO system to desalinate natural ground brackish water containing high Sr concentration (10.3 mg/L) in Tanzania [ 130 ]. It was found that the NF unit only had a Sr rejection of 55–67%, while RO can remove almost 100% of Sr, so the mixture of NF permeate and RO permeate can meet the USEPA guideline of 1.5 mg/L.…”
Section: Combined Utilization Of Nf With Other Membrane Technologymentioning
confidence: 99%
“…where , is the hindered diffusivity; , is the hindrance factor for convection, which are dimensionless coefficients in Nernst-Planck equations. They are made explicit in Equation (12) and Equation ( 13):…”
Section: Model Equationsmentioning
confidence: 99%
“…For both plots shown in Figure 6a,b, the concentration of the solute particles Cl − and Mg 2+ in the target layer of NF_PAN_Ti decreased as the particles moved from one side (feed) to another (permeate) (Table 3). solute particles' removal is the pore size rp of the NF_PAN_Ti active layer related to both hindrance coefficients already explained in the mathematical modeling equations, namely Ki,c for convection and Ki,d for diffusion, as it was clarified in Equations ( 8), (12), and (13) In…”
Section: Model Reassessment Of Salts Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are various aspects that require intensive research toward better understanding of the processes involved, further optimization of the technology, and increasing the applicability in other fields. For instance, the influences of operating pressure and groundwater pH on permselective properties of NF and RO membranes were studied in a pilot study by Cai et al [ 1 ]. The feed water was a natural groundwater from the Eslalei region in northern Tanzania with high strontium and organic matter contents.…”
mentioning
confidence: 99%